Investigating elastic properties of soft biological tissues. - Brusseau, E.
We have developed a signal processing technique to map the axial strain distribution occurring in a medium exposed to a mechanical compression with RF ultrasound signals. This method is based on an adaptive and iterative estimation of local scaling factors, via the exploitation of phase information.
Keywords: RF ultrasound signal compression; Adaptive estimation; Atherosclerosis; Axial strain imaging; Cumulative window displacement; Elastic properties; Elastography; Iterative estimation; Local scaling factors; Phase information; Postcompression signal segment; Signal processing technique; Soft biological tissues; Tissue motion; Two-layer intravascular cryogel phantom